Detecting ferroptosis and immune infiltration profiles in multiple system atrophy using postmortem brain tissue - Chen, Linxi; Mao, Lingqun; Lu, Hongsheng; Liu, Peng (Frontiers in Neuroscience, 2023)
The importance of ferroptosis and immune system has been mentioned in the pathogenesis of α-synucleinopathy. The α-synuclein-immunoreactive inclusions that primarily affect oligodendrocytes are the hallmark of MSA. Limited evidence implicates that iron and immune response are involved in the pathogenesis of MSA, which is associated with neurodegeneration and α-synuclein aggregation.The RNA sequencing data was collected from the Gene Expression Omnibus database. MSA-C related module genes were identified through weighted gene coexpression network analysis. Gene ontology and kyoto encyclopedia of genes and genomes analyses were performed to predict the potential molecular functions. The candidate ferroptosis-related genes associated with MSA-C was obtained using machine learning algorithm. CIBERSORT was used to estimate the compositional patterns of the 22 types of immune cells.The tissues for sequencing were extracted from postmortem cerebellar white matter tissues of 11 MSA-C patients and 47 healthy controls. The diagnostic ability of the six MSA-C related ferroptosis-related genes in discriminating MSA-C from the healthy controls demonstrated a favorable diagnostic value, with the AUC ranging from 0.662 to 0.791. The proportion of CD8 + T cells in MSA-C was significantly higher than in controls (P = 0.02). The proportion of NK cells resting in MSA-C was significantly higher than in controls (P = 0.011).The ferroptosis and T cells infiltration may be important pathways of disease development in MSA-C, and targeting therapies for these pathways may be disease modifying.